Wage Risk and the Skill Premium - Ctirad Slavík; Hakki Yazici (Center for Economic Studies and Ifo Institute (CESifo), 2020)
The skill premium has increased significantly in the United States in the last five decades. During the same period, individual wage risk has also increased. This paper proposes a mechanism through which a rise in wage risk increases the skill premium. Intuitively, a rise in uninsured wage risk increases precautionary savings, thereby boosting capital accumulation, which increases the skill premium due to capital-skill complementarity. Using a quantitative macroeconomic model, we find that the rise in wage risk observed between 1967 and 2010 increases the skill premium significantly. This finding is robust across a variety of model specifications.
Keywords: E25; J31; 330; skill premium; wage risk; capital-skill complementarity; precautionary savings